KONSEKUENSI MARRIED BY ACCIDENT DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Imawanto Imawanto; Edi Yanto; Mappanyompa Mappanyompa (Universitas Muhammadiyah Mataram, 2018)
This article discusses married by accident, which is a marriage that is forced to be carried out between a pair of men and women because the woman is already pregnant, their parents must marry her, in order to cover up their disgrace in the community. Using juridical-normative research methods. The results of the study are, first, the law of being married by accident is permitted both by positive law and Islamic law, secondly, the position of a married by accident child becomes a legitimate child in the perspective of positive law, and an illegitimate child in the perspective of Islamic law. Third, in a positive legal perspective, the legal guardianship and inheritance rights of a daughter from married by accident are her biological father and inheritance rights from her parents, whereas in Islamic legal perspective the child resulting from married by accident biological father has no right to give heirs and is not entitled also be the guardian of the child.keywords: Islamic law; married by accident; positive law. AbstrakArtikel ini membahas tentang married by accident, yaitu pernikahan yang terpaksa dilakukan antara sepasang laki-laki dan perempuan karena perempuannya sudah hamil terlebih dahulu, orang tua mereka harus menikahkannya, dalam rangka menutupi aib mereka di masyarakat. Menggunakan metode penelitian yuridis-normatif. Hasil penelitian, pertama, hukumnya married by accident di bolehkan baik oleh hukum positif dan hukum Islam, kedua, kedudukan anak married by accident menjadi anak sah dalam perspektrif hukum positif, dan anak tidak sah dalam perspektif hukum Islam. Ketiga, dalam perspektif hukum positif, hak wali dan hak waris anak perempuan dari married by accident adalah ayah biologisnya dan memperoleh hak waris dari kedua orang tuanya, sedangkan dalam perspektif hukum Islam anak hasil dari married by accident ayah biologis tidak berhak memberikan waris dan tidak berhak pula menjadi wali anak tersebut ketika menikah.kata kunci: hukum Islam; hukum positif; married by accident.